PENERAPAN MODEL KOOPERATIF TIPE STUDENTS TEAMS ACHIEVEMENT DIVISION (STAD) PADA SISWA SMA NEGERI 1 SUNGAI RAYA - Dwi Edi Budianto; Hairida Hairida; Ira Lestari (Universitas Tanjungpura, 2019)
Abstract This study aimed to determine whether there is a significant difference between student learning outcomes given cooperative learning model type Students Teams Achievement Division (STAD) with students given conventional learning on the redox reaction material, the effect of cooperative learning model type Students Teams Achievement Division (STAD) ) in improving student learning outcomes and student responses to cooperative learning models of the Students Teams Achievement Division (STAD) type on redox reaction material. The form of research used was a quasi-experimental research design